Spontaneous pneumomediastinum in a child due to 2009 pandemic influenza A (H1N1) virus - Ozdemir, Halil; Kendirli, Tanil; Dinçaslan, Handan Uğur; Ciftçi, Ergin; Ince, Erdal (The Turkish Journal of Pediatrics, 2010)
The 2009 pandemic influenza A (H1N1) virus spread throughout the world and caused different clinical situations. Here, we report a 4.5-year-old boy with spontaneous pneumomediastinum (SPM) complicating pneumonia associated with H1N1 virus. SPM could be associated with bronchial obstruction or necrotizing pneumonia, and the prognosis of patients with SPM associated with necrosis is worse than of patients with SPM associated with bronchial obstruction.